CICERO’S ECLECTICISM AND ORIGINAUTY - van Zyl, D.H. (Akroterion, 1990)
One of the most strenuous debates in regard to Cicero turns upon the comroversial subject of his eclecticism and originality, or lack of originality. Much of what is said on this subject, however, is simplistic or ill-considered, since it does not take account, on the one hand, of the relevant circumstances pertaining to Cicero’s eclecticism nor, on the other hand, of the basis upon which his originality should be adjudicated